Obedience as Belonging: Catholic Guilt and Frequent Confession in America - Stotts, Jonathan (Religions, 2019)
From the late 19th to the mid-20th century, the practice of private confession to a priest was a mainstay of Catholic parish life in the United States. By the 1970s, Catholics had largely abandoned the practice of private confession. One dominant narrative among Catholic theologians and clergy, identified chiefly with the papacy of John Paul II, attributes the decline in confession to the loss of healthy guilt that took place during the cultural upheaval of the 1960s. In conversation with the work of psychologist and philosopher Antoine Vergote, the present article challenges this narrative, arguing that a collective and unhealthy Catholic guilt existed among American Catholics well before the 1960s and in fact characterized the period in which private confession was practiced most frequently. I contend that obedience to moral prescriptions was not, for ordinary Catholics, part of an ethical program of self-reform but the condition for belonging to a church body that emphasized obedience. Finally, examining the relationship between weekly reception of communion and confession, I suggest that private confession emerged to support frequent communion, persisting only until the latter became standard practice among Catholics in the United States.